The association between unintended pregnancy and maternal mental health in rural China - Nan Wang; Yunjie Liu; Jianmin Ai; Jingchun Nie; Jie Yang (Frontiers in Public Health, 2025)
BackgroundUnintended pregnancies are common in rural China. However, the association between unintended pregnancy and maternal mental health remains poorly understood. This study aimed to assess the prevalence of unintended pregnancies, their association with mental health concerns, and the contributing factors in rural China.MethodsA cross-sectional design was used in this study. We included 473 pregnant women (age ranging from 18 to 45 years; local residency for at least 1 year; current pregnancy) from 10 counties in rural areas of Shaanxi Province, which is highly representative of rural northwest China in terms of economic status, geographical characteristics, and traditional culture. Mental health was assessed using the Depression, Anxiety, and Stress Scales-21 (DASS-21), widely recognized for its reliability, validity, and applicability in the Chinese context. Descriptive statistics and logistic regression analyses were employed to elucidate the prevalence of unintended pregnancy issues and explored their association with maternal mental health.ResultsThe prevalence rates of depression, anxiety, and stress in the full sample were 19.24, 23.68, and 10.99%, respectively. The proportion of unintended pregnancies was 41.44%, with significantly higher rates of depression, anxiety, and stress tendencies compared to intended pregnancy. Logistic regression analysis revealed a significant association between unintended pregnancy and an increased risk of anxiety tendency (OR = 1.96, 95% CI = 1.25–3.08, p = 0.004) as well as stress tendency (OR = 2.15, 95% CI = 1.15–4.02, p = 0.017). Furthermore, among women with unintended pregnancy, anxiety tendency was more pronounced among unemployed women (OR = 2.05, 95% CI = 1.25–3.35, p = 0.004), and co-residing with their mother-in-law (OR = 2.47, 95% CI = 1.40–4.38, p = 0.002). Similarly, stress tendency was more pronounced among unemployed women (OR = 2.20, 95% CI = 1.11–4.34, p = 0.023), and co-residing with their mother-in-law (OR = 2.60, 95% CI = 1.17–5.74, p = 0.018).ConclusionThe positive correlation exists between unintended pregnancy and maternal mental health risks. The high prevalence of unintended pregnancies underscores the need for policies aimed at reducing their occurrence, as well as interventions targeting mental health support to pregnant women.